Isolation of Lytic Bacteriophages from Environmental water samples specific to Vibrio cholerae; software-based analysis of whole-genome using bioinformatics tools - Arthi, Safwana Murshed (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2020.